Foreign Direct Investment and Social Sectors Development: A Review - Abu Bakar, Nor Aznin; Idrees, Sadia (iRASD, 2019)
Various studies in the past have examined the effect of foreign direct investment on economic growth, the key basic assumption common to these papers is that economic growth is a good proxy for welfare of both developed and developing countries. However, research on the influence of foreign direct investment on an expanded conception of socio-economic progress such as human development (measured by the human development index) is absent. This research paper presents the literature on foreign direct investment (FDI) and social sectors (health & education) development in the context of developing economies.